Sulfonated Nano-bentonit as Doping Material in Chtiosan/PVA membrane in Fuel cell Application - Ariesta, Nina (ALKIMIA, 2021)
Electrolyte membrane of fuel cell is the main component that plays a role in separating the reactants and being a means of transporting hydrogen ions produced by the anode reaction to the cathode so that the reaction at the cathode produces electrical energy. Chitosan/PVA/Nanobentonite based membrane was made of natural bentonite form Karang Tengah, Bogor. The study was conducted to know the effect of particle size of doping materials added to chitosan/PVA membrane for fuel cell. The method used in the experiment was casting method with variation of concentration of sulfonated bentonite. Then, membranes were namely C/PVA/n-ben 0.3, 0.6 and 0.9. The membrane that had been synthesized was identified by swelling test, proton conductivity test and cation exchange capacity test then characterized by FTIR, SEM and XRD. The result of the experiment showed the best swelling test was presented on the membrane with concentration of 0.9% sulfonated bentonite by 62.79% and the best proton conductivity test was shown on a membrane with a concentration of 0.6% sulfonated bentonite which was 2.24 x 10-6 S/cm, supported by the result of the cation exchange capacity data.